UJI ORGANOLEPTIK NUGGET DAGING SAPI DENGAN PENAMBAHAN TEPUNG DAUN KELOR - M. Aan Lutfi Hadiansyah; Nita opi ari kustanti; Resti Yuliana Rahmawati (Universitas Islam Balitar, 2020)
The main reason of this study was to determine the organoleptic test of beef nuggets with the addition of Moringa leaf flour. The questionnaire was taken at the Balitar Islamic University. Selection of respondents, namely selecting students who are currently studying to be respondents. The method of analysis uses the ANOVA method and the scoring system uses the hedodonic test method, where